Pemanfaatan Sosial Media Marketing dan Ecommerce untuk Meningkatkan Brand Awareness UMKM Di Desa Kedungjambe - Choirunnisa Choirunnisa; Faridatun Nikmah; Grace Salindeho; Hakim Mahdi Zakariya; Mochammad Adam Priyatmoko; Natasha Mardiani Alfons Heyden; Naufal Nur Ahmad; Nia Amalia; Novita Sari Makigawe; Safitri Dwi Ananda; Thalita Rizki Mirzanda Cahyaningrat; Tiara Meyla Seibina; Taufikurrahman Taufikurrahman (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This community service initiative aims to enhance the brand awareness and market competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Kedungjambe Village through digital marketing strategies. The study addresses the primary issue of limited consumer visibility, which hinders MSME growth. Training sessions were conducted to optimize the use of WhatsApp Business for effective customer communication and the Shopee e- commerce platform to expand market reach. MSME participants were guided in creating engaging promotional content, utilizing WhatsApp's broadcast features for direct interactions, and managing online stores on Shopee, including product descriptions, inventory, and sales analytics. Practical simulations on Shopee's features were provided to strengthen participants' understanding of e-commerce as a strategic sales channel. The results demonstrated a significant improvement in brand visibility, customer engagement, and sales performance among participating MSMEs. This initiative highlights the effectiveness of leveraging digital platforms like WhatsApp Business and Shopee to enhance MSME competitiveness, offering a sustainable model for rural business development.